THE THE EFFECT OF FINANCING FOR MUDHARABAH AND MUSYARAKAH RESULTS ON PROFITABILITY (ROA) (case study on Islamic commercial banks listed on the Indonesia Stock Exchange for the period 2017-2020) - Iis Silfi Fauziah; Wirman . (Jurnal Widya Akuntansi dan Keuangan, 2022)
This study was conducted with the aim of testing the effect of simultaneous and partial mudhrabah and musyarakah profit-sharing financing on the profitability of Islamic banking companies listed on the Indonesia Stock Exchange. In this study, data from Islamic banking companies were used as samples, namely 8 companies in the 2017-2020 period. This study used a quantitative approach model with secondary data in the form of financial statements of Islamic banking companies. The analytical technique used in this study is multiple analysis technique and processed using the SPSS 16 program. The results of this study indicate that mudharabah financing partially has a significant effect on Return On Assets (ROA) with a t-count value of 2.485 and has a significant value of 0.019. And Musyarakah partially does not have a significant effect on Return On Assets (ROA) with a t-count value of 0.892 and a significant value of 0.380. The two independent variables simultaneously affect Return On Assets (ROA) which has a calculated F value of 5.277 and a significant value of 0.01 or less than 0.05.